Exploring the Challenges and Perceptions of Online Education in Pakistani Higher Education Institutions Amidst the COVID-19 Pandemic - Zohaib Hassan Sain; Rene. M. Babiera II (International Journal of Scientific Multidisciplinary Research, 2023)
Amid the global COVID-19 pandemic, the widespread adoption of online learning has become a prominent feature of education across the nation. This study delves into the experiences of both teachers and students in adapting to online learning, employing an online survey methodology. Given the unprecedented nature of this educational shift, it was essential to investigate how teachers and students, unaccustomed to this mode of instruction, navigated the challenges posed by the pandemic. The research collected data from public and private universities in Lahore, with a total of 430 participants (20 teachers and 410 students) contributing to the study. The online survey identified key areas crucial to the satisfaction of both teachers and students in the online learning environment, including student-faculty communication, technical support, well-organized online classes, and adaptations to facilitate practical coursework. This research represents an exploration of the dynamic and multifaceted nature of online learning in the context of a global health crisis